A novel strategy for multiplexed immunoassay of tumor markers based on electrochemiluminescence coupled with cyclic voltammetry using graphene-polymer nanotags. (10th July 2015) - Feng, Xiaobin; Gan, Ning; Zhang, Huairong; Yan, Qing; Li, Tianhua; Cao, Yuting; Hu, Futao; Yu, Hongwei; Jiang, Qianli
Graphical abstract: Highlights: A novel immunosensing strategy based on ECL coupled with CV was designed. The rGO-Hemin/Pt-PowerVision nanocomposites connect with CEA-antibodies was employed as CV labels. The rGO-Poly-L-lysine/Ru(bpy)3 2+ -silica@Au nano composites connect with AFP-antibodies was used as ECL labels. The CV and ECL labels can display high signal intensity at different potentials. The sensor can simultaneous detect two tumor markers in pg/mL order of magnitude in serums. Abstract: A novel immunosensing strategy was designed to simultaneous analysis of alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA) by using electrochemiluminescence (ECL) coupled with cyclic voltammetry (CV) methods. In the assay, two kinds of graphene-polymer based nanotags were fabricated for tumor makers (TMs) distinction and signal amplification. The CV nanotags (rGO-H/Pt-PV) were prepared by immobilizing PowerVision doped platium nanoparticles complex (Pt-PV) on the surface of hemin modified reduced graphene oxide sheets (rGO-H) composites. Pt-PV is a kind of compact enzyme-linker linear polymer with a great number of horseradish peroxidase and was then modified with Pt NPs, which have the double catalyst abilities of the reduction of H2 O2 at cathode potential in the presence of hemin. The ECL signal nanotags (rGO-PLL/Ru-Si@Au) were prepared by immobilizing Ru(bpy)3 2+ -silica doped gold nanoparticles composites (Ru-Si@Au) on reduced graphene oxide sheets (rGO) using poly-L-lysine (PLL) as linker and co-reactant. Moreover, the biosensor platform was prepared by co-immobilizing CEA and AFP's first antibody on gold nanoparticles modified glassy carbon electrode. Based on a sandwich-type immunoreaction, CEA and AFP, CV and ECL nanotags were conjugated on the electrode sequentially. In one-cycle voltammetric test, the CV nanotags produce a cathode current signal at −0.3 V and the ECL nanotags emit an anode luminescent signal at 1.25 V, which were respectively used for CEA and AFP detections. Under the optimum conditions, CEA and AFP could be assayed in the linear ranges of 5 pg mL −1 - 40 ng mL −1 and 3 pg mL −1 - 50 ng mL −1, with the detection limits of 1 pg mL −1 and 0.5 pg mL −1 (at 3sB ), respectively. More importantly, this designed method was used in real serum samples analysis and has significant potential for TMs detection in a clinical laboratory setting.